Association between neck circumference and non-alcoholic fatty liver disease: cross-sectional analysis from ELSA-Brasil - Santos, Laura Luiza Menezes; Diniz, Maria de Fátima Haueisen Sander; Goulart, Alessandra Carvalho; Barreto, Sandhi Maria; Figueiredo, Roberta Carvalho (São Paulo Medical Journal, 2022)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) has become a public health problem worldwide. Neck circumference (NC) is a simple anthropometric adiposity parameter that has been correlated with cardiometabolic disorders like NAFLD. OBJECTIVES: To investigate the association between NC and NAFLD, considering their obesity-modifying effect, among participants from the Longitudinal Study of Adult Health (ELSA-Brasil) baseline study. DESIGN AND SETTINGS: Cross-sectional study at the ELSA-Brasil centers of six public research institutions. METHODS: This analysis was conducted on 5,187 women and 4,270 men of mean age 51.8 (± 9.2) years. Anthropometric indexes (NC, waist circumference [WC] and body mass index [BMI]), biochemical and clinical parameters (diabetes, hypertension and dyslipidemia) and hepatic ultrasound were measured. The association between NC and NAFLD was estimated using multinomial logistic regression, considering potential confounding effects (age, WC, diabetes, hypertension and dyslipidemia). Effect modification was investigated by including the interaction term NC x BMI in the final model. RESULTS: The frequency of NAFLD and mean value of NC were 33.6% and 33.9 (± 2.5) cm in women, and 45.8% and 39.4 (± 2.8) cm in men, respectively. Even after all adjustments, larger NC was associated with a greater chance of moderate/severe NAFLD (1.16; 95% confidence interval [CI] for women; 1.05, 95% CI for men; P < 0.001). Presence of multiplicative interaction between NC and BMI (P < 0.001) was also observed. CONCLUSION: NC was positively associated with NAFLD in both sexes, regardless of traditional adiposity indexes such as BMI and WC. The magnitude of the association was more pronounced among women.